Banpres Program Planning Policy Productive Micro Business Ministry of Cooperations and Smes During the Covid-19 Pandemic in Supporting State Defense - Fitri Rinaldi; Syamsul Maarif; Suyono Thamrin; Asep Adang Supriyadi (Budapest International Research and Critics University, 2022)
The Government of Indonesia has a number of National Economic Recovery (PEN) programs. One of them is the Banpres program for Productive Micro Enterprises (BPUM). The BPUM program has been implemented by the Ministry of Cooperatives and MSMEs since August 2021 and will be continued in 2021 with the consideration that the COVID-19 pandemic is still hitting Indonesia. In the COVID-19 pandemic situation, if the affected MSME conditions are not handled properly it can affect the level of poverty, unemployment, and economic inequality. Based on this explanation, it is very important to conduct research on Policy Planning for the Banpres Program for Productive Micro Enterprises at the Ministry of Cooperatives and SMEs during the COVID-19 pandemic in support of national defense. The research method used is included in the assessment research or Evaluation Research. The research locations are the Ministry of Cooperatives and SMEs, the Ministry of Defense, Bappenas, and the Ministry of Finance and local governments. The results of the study show that the spread of Corona Virus Disease (Covid-19) since 2019 has had very significant implications for the Indonesian economy. This situation has an impact on decreasing demand for labor, controlling income and public consumption, thereby reducing the demand for cooperative and MSME products. Following up on the impact of the COVID-19 pandemic, the Government continues to encourage the realization of the National Economic Recovery Program (PEN), through program extensions, acceleration of new proposals, program redesign and adjustment, as well as simplification of procedures. Micro, small and medium enterprises (MSMEs) play an important role in the Indonesian economy. Future growth of Cooperatives and SMEs is directed at strengthening economic resilience to support quality growth with the main objectives of increasing value, competition, investment, exports, import substitution, and expanding job opportunities by strengthening cooperatives, micro, small and medium enterprises. (MSMEs) and the business world.